Diversity and succession pattern of forensically important dipteran species associated with organophosphate pesticides-intoxicated rat carcasses in Sarawak, Malaysia - Nor Aliza Abdul Rahim,; Marlini Othman,; Madinah Adrus,; Zainab Ngaini, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research aimed to study the decomposition process of organophosphate-intoxicated rat carcasses and the succession pattern of associated insects at a secondary forest in Kuching, Sarawak, Malaysia. The animal model, Rattus norvegicus, weighing around 180-200g were assigned in T1 and T2 groups and were given LD50 dosage of organophosphate, glyphosate, and chlorpyrifos via oral administration, respectively. Sixty minutes after oral administration, the rats were euthanized and brought to the study site. The rat carcasses were monitored daily and the carrion insects were collected throughout the decomposition process. From five trials of experiments, a total of 1454 individual flies were collected, belonging to three families and 10 species. The highest number of fly species collected was Chrysomya rufifacies (75.03%) being the predominant species infesting the carcasses. The dipteran diversity and succession pattern were similar for all groups of carcasses, even though insect abundance were the least in T2 carcasses. Five stages of decomposition were observed in all rat carcasses, with longer decomposition duration in intoxicated carcasses (T1: 7.85±0.51 and T2: 15.8±2.82 days) compared to the control group (7.25±0.59 days). In conclusion, the organophosphate has altered the decomposition duration and the number of flies infesting the carcasses especially on chlorpyrifos-intoxicated carcasses. This work provides relevant information regarding the insect’s succession pattern and the changes in the decomposition period which may assist in the determination of post-mortem interval time in future investigation processes when organophosphate poisoning is suspected.